Heart transplantation for advanced heart failure due to cardiac sarcoidosis - Theofilogiannakos, Efstratios; Pettit, Stephen James; Ghazi, Azmee; Rassl, Doris; Lewis, Clive; Parameshwar, Jayan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background.  Selected patients with cardiac sarcoidosis undergo heart transplantation, but outcomes may be adversely affected by recurrent cardiac sarcoidosis or progressive extra-cardiac sarcoidosis. Objectives.  We present our single-center experience of patients with cardiac sarcoidosis who underwent heart transplantation.Methods.  Consecutive patients that underwent heart transplantation between 1990 and 2012 were assessed.  Cardiac sarcoidosis was defined by the presence of multiple non-caseating epithelioid cell granulomata in the explanted heart.  Baseline characteristics and clinical outcomes were compared with a control group without cardiac sarcoidosis that underwent heart transplantation during this period.Results.  901 patients underwent heart transplantation during the study period, of whom 4 patients had a pre-transplant diagnosis of cardiac sarcoidosis and 8 patients had sarcoidosis identified in the explanted heart.  Patients with cardiac sarcoidosis had excellent post-transplant outcomes with survival of 92% at one year and 83% at five years.  Survival was similar to patients that underwent heart transplantation for an alternate diagnosis.  We did not encounter recurrent cardiac sarcoidosis or progressive extra-cardiac sarcoidosis during 1001 months of follow-up.Conclusions.  Carefully selected patients with advanced heart failure due to cardiac sarcoidosis have an acceptable outcome after transplantation.  Cardiologists should be aware that reported experience of transplantation for cardiac sarcoidosis mostly represents isolated cardiac sarcoidosis that was only diagnosed at pathological examination of the explanted heart.